The Role of Cucurbitacins in Combating Cancers: A Mechanistic Review - Alsayari, Abdulrhman; Halaweish, Fathi T; Gurusamy, Narasimman (Pharmacognosy Reviews)
Cucurbitacins are highly oxidized tetracyclic triterpenoids from the Cucurbitaceae families. Several cucurbitacins, such as B, D, E, I, R, IIa, and dihydrocucurbitacin B, have been shown to possess antiproliferative and anticancer activities. Mechanistically, cucurbitacins induce cell cycle arrest at the G2/M phase and induce apoptosis through several mechanisms, such as the production of reactive oxygen species. In addition, they can inhibit the migration and invasion of cancer cells. Consistently, cucurbitacins have been shown to inhibit the Janus kinase‑mediated activation of the transcription factor, signal transducer and activator of transcription. In addition, other receptor‑mediated signaling pathways, such as ErbB, human epidermal growth factor receptor 2, and integrins, have also been inhibited by the cucurbitacin on cancer cells. Cucurbitacin treatments for various types of cancer have been shown to disrupt the cytoskeletal components such as actin, inhibit the expression of the proto‑oncogenic proteins such as c‑myc, and induce the expression of tumor suppressor proteins such as p53. Importantly, the synergistic anticancer activities of cucurbitacins have been observed when combined with established chemotherapeutic drugs, such as imatinib mesylate, paclitaxel, docetaxel, and gemcitabine. Cucurbitacins are a promising anticancer agent and can potentiate the effect of current chemotherapy drugs as well as reduce the serious side effects of these drugs.
Keywords: Apoptosis; cancer; cell cycle arrest; cucurbitacin; molecular mechanism; p53